The Evidentiary Strength of Electronic Signatures in Fiduciary Security Deeds within Financing Institutions: An Analysis of Legal Certainty and Judicial Practice in Indonesia - Muhammad Yusuf Y. Badar; Evita Isretno Israhadi (Ridwan Institute, 2026)
Within this digital legal environment, electronic signatures (e-signatures) serve a crucial role as authentication tools that verify the integrity and authorship of electronic documents. Although Indonesian legislation has formally acknowledged electronic signatures as legitimate evidence through the Electronic Information and Transactions Law, their application in documents associated with notarial deeds, such as fiduciary security deeds and Powers of Attorney to Create Fiduciary Security (SKMF), continues to generate legal debate. This study seeks to examine the regulatory framework governing electronic signatures within the Indonesian legal system, evaluate their evidentiary value in judicial practice, and analyze the legal consequences of their use in relation to the validity of fiduciary security deeds. The research employed a normative legal research method, utilizing both statutory and conceptual approaches. The findings indicate that certified electronic signatures possess strong evidentiary authority because they rely on cryptographic infrastructure and electronic certificates issued by authorized Electronic Certification Authorities (PSrE). This technological framework ensures the principle of non-repudiation, thereby strengthening their reliability as legal evidence. In contrast, uncertified electronic signatures demonstrate comparatively weaker evidentiary value, as their authenticity can more easily be challenged by disputing parties. The study concludes that the utilization of certified electronic signatures in the SKMF constitutes an essential requirement for safeguarding the authenticity of fiduciary security deeds while simultaneously ensuring legal certainty for financing institutions operating within Indonesia’s emerging digital fiduciary framework.